(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Not only in school textbooks on organic chemistry, but also in university textbooks, the structural formulas of only the initial members of the homologous series of organic compounds are given, and the isomers of other members of the homologous series are given under the total number. In the electronic textbook Yusupova D.S., Abdullaeva M.D. “Isomerism and nomenclature of organic compounds”, the structural formulas of 545 isomers included in this total number are written. For the purpose of an in-depth study of isomerism and the nomenclature of organic compounds in the school chemistry course, a pedagogical experiment is being carried out using a written electronic textbook. As an example from the lessons of the pedagogical experiment, the development of a lesson on the topic “Isomerism and the nomenclature of alkanes”, which is conducted using information technology, is given.